EVALUASI PENGGUNAAN ANTIBIOTIK PROFILAKSIS PADA PASIEN BEDAH SESAR (SECTIO CAESAREA) DI RSUD ULIN BANJARMASIN TAHUN 2017 - Saftia Aryzki; Hidayatun Nisa; Dian Yunita Gamaliana (Jurnal Ilmiah Manuntung, 2019)
Cesarean section (Sectio Caesarea) is an attempt to remove the fetus through surgery on the abdominal wall and uterus. The use of inappropriate prophylactic antibiotics will lead to infection and resistance. The purpose of this study was to determine prophylactic antibiotic use, in cesarean section patients, to know prophylactic antibiotic use in cesarean section patients in accordance with antibiotic use guidelines (PPAB) Ulin Hospital in 2017, to know prophylactic antibiotic use in cesarean section patients in accordance with Permenkes RI Number 2406 / PER / XII / 2011. This research is a non-experimental type of descriptive study retrospectively by taking medical record data of cesarean section patients at Ulin Banjarmasin Hospital in 2017 with saturated sampling method, obtained a population of 99 medical records of cesarean section with a total sample of 99 medical records. The use of prophylactic antibiotics in Ulin Banjarmasin Public Hospital is a class of third generation cephalosporins namely ceftriaxone and cefotaxime with doses of 1-2 grams / day and duration of 3-5 days. Comparison of the percentage of prophylactic antibiotic use with the guidelines for drug use in Ulin Hospital in Banjarmasin in 2017 is the name and class of 100% is appropriate and 0% is not appropriate, the dose is 100% appropriate and 0% is not appropriate, the duration of administration is 69.70% is appropriate and 30.30% is not corresponding. Comparison of the percentage of prophylactic antibiotic use with Permenkes RI Number 2406 / PER / XII / 2011 is the name and class of 0% is appropriate and 100% is not appropriate, the dose is 0% is appropriate and 100% is not appropriate, the duration of giving 0% is appropriate and 100 % it is not in accordance with.